Angiotensin converting enzyme and dipeptidyl peptidase-IV inhibitory activities of transglutaminase treated sodium caseinate hydrolysates. (March 2018) - Cermeño, Maria; O'Brien, Nora; FitzGerald, Richard J.
Abstract: Angiotensin converting enzyme (ACE) and dipeptidyl peptidase-IV (DPP-IV) inhibitory activities of cross-linked and non-cross-linked sodium caseinate (NaCN) hydrolysates were studied. Three different samples were generated: NaCN hydrolysed with Prolyve 1000™ (Prolyve), NaCN cross-linked with transglutaminase (TGase) pre-Prolyve hydrolysis and NaCN cross-linked post-Prolyve hydrolysis. Gel filtration and reverse phase HPLC analysis of the resulting samples indicated that the hydrolysates had similar peptide profiles. Hydrolysates showed higher ( p  < 0.05) ACE and DPP-IV inhibitory activity compared with intact protein, but no significant ( p  > 0.05) differences in activity were found between cross-linked and non-cross-linked hydrolysate samples. Hydrolysate IC50 values for ACE and DPP-IV inhibition ranged from 0.10 to 0.17 mg mL −1 and 0.85–1.18 mg mL −1, respectively. Simulated gastrointestinal digestion had no significant ( p  > 0.05) effect on the bioactivities of the hydrolysates. The results demonstrated that incubation with TGase before or after NaCN hydrolysis with Prolyve had no effect on ACE or DPP-IV inhibitory activities.